Faux Pas Recognition and Executive Processes in Patients with Alcohol Use Disorder: Toward an Investigation of Interindividual Heterogeneity. (17th September 2021) - Schmid, Franca; Moreau, Franklin; Benzerouk, Farid; Raucher-Chéné, Delphine; Kaladjian, Arthur; Gierski, Fabien; Henry, Audrey
Abstract: Objective: Impairment of executive functions (EF) has been documented for decades in patients with alcohol use disorders (AUD), while more recent studies have also reported impaired theory of mind. Both have been associated with negative outcomes, particularly a high risk of relapse. However, the interrelatedness of EF and theory of mind impairments remains subject to debate. Method: About 19 AUD outpatients and 20 healthy controls (HC) were asked to complete measures of motor inhibition, mental flexibility, and updating to assess EF, and the faux pas test to assess theory of mind. Results: As expected, patients' mean performances on EF and faux pas measures were poorer than those of HC. Correlational analyses revealed that executive processes were differentially related to faux pas subscores. Additional single-case analyses corroborated the strong association between EF and faux pas interpretation, as patients with AUD mostly had congruent performances (i.e., both EF and faux pas impaired or both EF and faux pas preserved). Conclusions: This study highlights the interrelatedness of EF and faux pas performances in AUD, but also emphasizes the incomplete overlap of the cognitive processes involved in these tasks, with heterogeneous patterns of association. Based on these findings, tailored cognitive rehabilitation programs that simultaneously target EF and faux pas recognition could be developed to favor patients' social inclusion and reduce the risk of relapse. Results also argue in favor of systematic screening for EF and theory of mind impairments among AUD patients.